“Cool” and “Hot” Executive Functions in Patients With a Predominance of Negative Schizophrenic Symptoms - Ruiz-Castañeda, Pamela; Santiago-Molina, Encarnación; Aguirre-Loaiza, Haney; Daza González, María Teresa (Frontiers in Psychology, 2020)
Background. Patients with psychosis often present significant neurocognitive deficits, with executive function deficits (FFEE) being one of the most relevant cognitive impairments with the greatest impact on the functioning of their daily lives. However, and although various findings of executive involvement were reported, it is not entirely clear whether there is a differential pattern of involvement according to the clinical symptoms or whether the deficits occur in all or only in some subcomponents of FFEE. Objective: The present study had a double objective: to study the specific deficits in the cool and hot FFEE in a group of psychotic patients with a predominance of negative symptoms; and determine the possible associations between the performance of the patients in the cool an hot FFEE tasks with the negative symptoms, and with the behavioral alterations associated with the dysexecutive syndrome. Method: 66 participants, 33 psychotic patients with a predominance of negative symptoms and 33 healthy control subjects matched in gender, age and educational level participated. Both groups were administered 4 cool EEFF tasks (coding/maintenance and updating of information in working memory, ability to change the mental set and planning), and 3 hot EEFF tasks (decision making in situations of uncertainty, recognition of emotions through facial expressions and theory of mind). In the group of patients, the NS were evaluated through the Scale for the Evaluation of Negative Symptoms (SANS), and the behavioral alterations associated with dysexecutive syndrome through the subscale of “Executive Dysfunction” of the Frontal Systems Behavior Scale. Results: Patients performed worse on three cool EEFF tasks and on two of the hot EEFF tasks. Additionally, we found a correlation between the SANS score and the “executive dysfunction” subscale, with the cold EEFF task that measures planning. Conclusions: Our findings showed that in psychotic patients with a predominance of negative symptoms, both the cognitive (cool) and emotional (hot) components of executive functions are affected. The results found reinforce the need for a cognitive rehabilitation treatment of the executive components of the working memory and of those more socio-emotional aspects.